The Transformation of the Role of Dedes in Modern Times (Journal of Alevism-Bektashism Studies, 2020)
This article deals with the transformation of the dede institution, one of the basic institutions of Alevism, throughout the urbanization. Dede institution played a primary role in the survival of Alevism until today. That is why it wouldn’t be an exaggeration to say that this institution is of key importance for an understanding of Alevism in Anatolia. Dedes have moved away from their roles in dede-talib relations, which are based on ocaks in traditional life, and also from their traditional functions due to urbanization. Today, cemevis and cultural centers in Turkey and the urban centers around Europe are widely run by associations and foundations. It is now clear that traditional institutions which had a significant power in the past, such as ocak institution, have been transformed. The socio-economic transformation caused by urbanization has also caused significant effects on the life of Alevis. It is necessary to compare the status of dede institution in the past with its current status in order to better understand this situation. There are great differences between the new and the old qualifications and functions of dedes in the new social order. The functions of Dede institution have either disappeared with time, or have continued with various changes along with the new conditions and new needs of the society. The change is still continuing.